1999
DOI: 10.1159/000026226
|View full text |Cite
|
Sign up to set email alerts
|

Use of Latent Class Analyses for the Estimation of Prevalence of Cognitive Impairment, and Signs of Stroke and Parkinson’s Disease among African-American Elderly of Central Harlem: Results of the Harlem Aging Project

Abstract: A probability sample (response rate of 79.4%) of 164 African-American elderly residing in central Harlem was assessed using several standard cognitive screening measures and scales measuring stroke and Parkinson’s symptoms, respectively. Both traditional cutting scores and the methods of latent class analysis were used to estimate point prevalence. The latent class prevalence ratio estimates range from 10 to 14%. The confidence intervals for cognitive impairment ranged from 5 to 18% with an average estimate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
(56 reference statements)
1
11
0
Order By: Relevance
“…D'Uva (2005) emphasizes the role of latent classes for modeling health care utilization. Teresia et al (1999) estimate the prevalence of cognitive impairment, signs of stroke and Parkinson's disease. Li et al (2003) estimate the prevalence of fear of falling in the elderly related to functional ability and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…D'Uva (2005) emphasizes the role of latent classes for modeling health care utilization. Teresia et al (1999) estimate the prevalence of cognitive impairment, signs of stroke and Parkinson's disease. Li et al (2003) estimate the prevalence of fear of falling in the elderly related to functional ability and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies based on reviews of hospital or outpatient records [4,7,9] or on US mortality data [17] reached similar conclusions, but all of these are potentially subject to ascertainment and diagnostic bias: racial differences in access to and use of medical care are well described [18] , and PD is underdiagnosed in general and, in particular, among African-Americans [5,6] .…”
Section: Discussionmentioning
confidence: 89%
“…suggested that African and African-American populations have a lower prevalence of PD [4][5][6][7][8][9][10][11][12][13][14] . However, these studies have been limited by small sample size, ascertainment bias in clinic-based samples and possible racial differences in access to medical care [8] .…”
mentioning
confidence: 99%
“…Although this study was not an evaluation of a screening instrument, the studies reporting the responses to similar questionnaires were all either for screening validation or prevalence surveys [4-7,28,31]. Positive responses are compared between the individuals in the sub-cohort who answered all symptoms questions, for above and below 65 years of age, and the unaffected controls from other studies.…”
Section: Discussionmentioning
confidence: 99%